THE STAGE OF ALCOHOL ABUSE BASED ON TYPE OF PERSONALITY TO ADOLESCENT OF SCOOTER COMMUNITY BANGKIT IN KEDIRI - Pitasari, Lusy; Kurniajati, Sandy (Jurnal Penelitian STIKES Kediri, 2013)
Adolescent community their tends to abuse alcohol. The objective of this research describing the stage of alcohol abuse based on type of personality to adolescents. The research design was descriptive. The population was all adolescents in the. Scooter Community Bangkit in Kediri. The samples were 30 respondents quota sampling. The variables were the stage of alcohol abuse and type of personality. The was collected using questionnaire and  analyzed using Frequency Distribution. The results showed that the adolescents of scooter community majority (100%)  alcohol abuse happened on the stage of social and recreational (33.3%) and experimental stage (23.3%). Meanwhile the type of personality that supported the stage of alcohol abuse phlegmatic type (36.7%) and melancholic type (26.7%). It could be concluded  adolescent of Scooter  majority on the stage of alcohol abuse was on the of social and recreational. Meanwhile phlegmatic and melancholic types dominant against alcohol abuse.